Technology, economies of scale and average size of industrial plants: Some further cross-country evidence - Ranadev Banerji (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1976)
Sargant Florence pointed out long ago that broad technological factors seemed to underlie inter-industry differences in the typical size of plants. Much attention has been paid in several other recent studies to factors affecting average size of plants in industries and its variations among countries and over time. Their findings establish the important point that what lies at the heart of the matter is the different degrees to which countries are able to realize economies of scale in production. While the importance of technological economies in the shaping of the industry's scale curve is well recognised in theoretical literature, the empirical studies have, however, paid little explicit attention to this factor as a determinant of plant size differences across countries. This paper examines the hypothesis that average plant size of industries is an increasing function of the level of capital intensity in production. In testing this hypothesis, the capital intensity pattern and average plant size of industries are compared for countries at different levels of economic development. This approach has two advantages. First, the observed differences in the level of capital intensity are likely to be most pronounced when countries at different levels of technological development are considered. Secondly, it throws some light on the question of the relationship of economic development to the size of industrial plant, an issue of considerable interest in itself. This paper differs in two further respects from other studies. First, the concept of average size (measured by employment) used here takes account of the entire distribution of plants, including the small-sized plants. Use is made of the lognormal distribution model in estimating the average size. Secondly, the scope of the present sample is also broader than has been the case so far average plant sizes by industries are compared for 23 nations, including many less developed.
Keywords: 330